Grounding leadership theory and research : issues, perspectives and methods - Parry, Ken W.; Meindl, James R., 1952-2004 (Leadership horizons series ;, 2002)
This series is devoted to new developments and fresh perspectives in theory and research on leadership, within the context of continuing and emerging organizational issues. The series embraces a broad definition of leadership phenomena, including a focus on people, positions, processes, relationships, and situations. The series will advance an applied scholarship model, wherein sound academic work is connected, either directly or more speculatively, to real-world problems and controversies. The series seeks to promote work that aggressively pushes beyond current leadership orthodoxy and critically examines conventional thinking and practices. The series will represent a wide range of organizational, industry, national and global leadership issues. The series will feature entire volumes written by authors and edited volumes with multiple contributors. The series is intended to appeal to academic researchers and professional analysts, and to university instructors looking for thought provoking reference material for classroom use.